PENGARUH MANAJEMEN STRES TERHADAP KINERJA PEGAWAI DAN DOSEN DI FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Suarga; Alifa, Resky Nur (Department of Islamic Education Management, 2022)
The purpose of this study was to determine 1) Overview of Stress Management for Employees and Lecturers at the Faculty of Tarbiyah and Teacher Training (FTK) UIN Alauddin Makassar, 2) Overview of Employee and Lecturer Performance at the Faculty of Tarbiyah and Teacher Training (FTK) UIN Alauddin Makassar, 3) Effects of Stress Management Against the Performance of Employees and Lecturers at the Faculty of Tarbiyah and Teacher Training (FTK) UIN Alauddin Makassar. This type of research is a type of quantitative research using the explanatory research method. The population in this study was 198 people is taken which is of 51 employees and 147lecturer Faculty of Tarbiyah and Teacher Training, and then taken sample as many as 66 people is taken which is a combination of 51 employees and 15 lecturers. The sampling technique used is saturated sampling and proportional random sampling. The research instrument used in this study was a questionnaire/questionnaire and documentation. The results of this study indicate that 1) Stress Management is in the medium category with a percentage of 70%, 2) Employee performance is in the medium category with a total percentage of 41%, and 3) There is a significant positive effect between stress management and the performance of employees and lecturers from the results of the analysis using SPSS. Thus, there is still a need for efforts to continue to improve stress management so that employee performance is increasing at the Tarbiyah and Teacher Training Faculty of UIN Alauddin Makassar.